Building Quality of Human Capital through Pre-Marital School for Teenagers in Ciherang Village - Yulina Eva Riany; Mintarti; Rindang Matoati; Ira Mustika; Athaya Nadiya Asyhar; Siva Nadia; Ramadhansyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The number of child marriages in Indonesia continues to increase and Indonesia is in the top 10 with the highest number of child marriages in the world. Pre-Marital School is a non-formal learning about marriage preparation for adolescents to gain knowledge and readiness before entering family life. The objectives of the Pre-Marital School are to reduce the high rate of child marriage, change adolescents' perception of family welfare, increase adolescents' knowledge related to family welfare and family functions, family nutrition, and improve family welfare. This study used action research method, which is organizing measurable action activities for teenagers in Ciherang Village, Bogor Regency, West Java. The number of participants involved was 16 teenagers. The data collected were pre-test and post-test data. The data was processed with SPPS by looking at the average change in knowledge. The results show that there has been a change in adolescents' perceptions about the importance of forming a prosperous family, an increase in adolescents' knowledge about the minimum age of marriage, indicators of prosperous family stages and family functions, and an increase in knowledge about family nutrition in adolescents. The success of this program shows that it is necessary to re-conduct similar programs that can be carried out in other areas. It is hoped that this program can reduce the number of child marriages in Indonesia.